LABOUR MARKET REGULATION TOOLS AND INSTRUMENTS FOR THE BORDER DISTRICTS OF THE WESTERN REGIONS OF UKRAINE - Iliash, Olha (Journal of European Economy, 2017)
There was determined the necessity to increase the efficiency of labour market regulation in the border districts of the western regions of Ukraine. There were identified the drawbacks of the labour market regulation mechanism and the irrationality of social and demographic development of the border districts.There were substantiated the measures aimed to increase the regulation efficiency and provide the labour market development in the border districts.